(untitled) (Dhaka University Law Journal, 2025)
In commercial transactions, the merchants not only exchange terms of contract that are essential in negotiation, like quantity, price, date of delivery, etc., they also exchange ‘standard’ or ‘boilerplate terms’ in pre-printed forms to conclude the contract. A battle of forms arises when the buyers and sellers exchange conflicting standard terms between them, yet they proceed with the performance based on what they construe to be the contract terms. However, these discrepancies, though they appear innocuous at the beginning, often turn out to be the bone of contention as soon as the dispute arises. The pivotal questions before the court in a battle of forms dispute appear to be primarily the following:(1) Whether a contract is formed? (2) If yes, whose terms shall govern it? Put more precisely, what are its terms?’ The traditional rules of contract formation usually favours the ‘mirror image rule’ and its derivative ‘last shot doctrine’. However, both approaches lose their practicality since modern transactions are mostly conducted without paying attention to what is written in the standardised forms. This article delves into the comparison between the two major doctrines used to resolve these questions and suggests a ‘knock-out’ approach where the conflicting terms are eliminated and substituted with gap-filling provisions. On analysing the laws and jurisprudence developed in several countries adopting the intention-oriented view, it explains why such an approach serves the business purpose better while keeping the parties out of the battle of forms. Finally, it examines the limitations in the current framework of the Contract Act, 1872 and recommends amendment of the same to make it compatible in incorporating the ‘knock-out’ rule to accommodate the global trends of commercial negotiations and contract formation. Dhaka University Law Journal Vol.35, Issue.2, December 2024 P. 1-23